Laser surface cleaning of stainless steel - Ang, Cheow Tee (2019)
Appropriate surface cleaning is crucial for confirming quality of manufacturing and remanufacturing. Thermal cleaning, mechanical abrasive cleaning and chemical cleaning are the common processes used in the industry as it can removes dirt and contaminants, however these process can bring damage to the substrate and it may add to environmental hazards. On the contrary, laser cleaning are considerable more environmentally friendly as elimination of surface contaminants or oxides abolished the use of chemicals or other additives. Laser cleaning operate on moving short laser pulses to produce micro-plasma bursts and shockwaves that leads to direct sublimation and ejection of the target material. This project study laser ablation, characterization of the surfaces after the laser ablation, and analyses of results for the process optimization on stainless steel.